Absolute translativity of generalized Norlund mean / Amjed Zraiqat - Zraiqat, Amjed (2015)
In this paper, two results involving left and right translativity for absolute generalized Nörlund mean (N,p,q) are established. Two interesting non-trivial examples to show that (N,p,q) may have only one-side translative being constructed, one non-trivial example to show that (N,p,q) may be translative is given, and one non-trivial example to show that(N,p,q) is non-translative from the left nor do from the right is constructed.